Definition and Functions of Ecological Ethics - Kalenda, Česlovas (Problemos, 2003)
The article discusses the conditions of the rise of ecological ethics and its place in the applied ethics. Ecological ethics is considered both as scientific exploratory and academically as established discipline, having independent status and object. The rise of ecological ethics was determined by increasing contradictions between the expansion of technological civi- lization and natural evolution, between technosphcre and biosphere. The topic of this ethics was bom and developed at the junction of humanities and natural sciences, in the interaction of humanism and natura- lism. Ecological ethics carries out very important func- tions in the society, the most noteworthy of them being the integration of „two cultures“ - traditional - humanitarian, and the new one - scientific.
Keywords: Albert Schweitzer; Aldo beopold; Renselaer van Potter; applied ethics; ecological ethics